Critical care nurses' lived experience of caring: a hermeneutic investigation - Papathanassoglou, Elizabeth; Vouzavali, Foteini; Karanikola, Maria (My University, 2009)
Purpose: Despite the increasing research interest in patients' lived-experience of critical illness, the experiences of nurses who accompany individuals in these intense trajectories remain concealed. The purpose was to explore: I) nurses' perceptions of how caring for the critically ill affected their own personal experiences, lives, personalities, meanings, values and overall their holistic "self", and II) nurses' perceptions and meanings regarding the inter-personal therapeutic relationship with critically ill individuals. Methods: A qualitative phenomenological design with the hermeneutic approach was employed. Narrative descriptions and reflections of nurses? experiences were collected through repeated one-to-one and focus group phenomenological interviews which were repeated to the point of theoretical Analysis of transcribed interviews was carried out by independent analysis and focused discussions. Munhall's (1994) criteria were employed to ensure rigor. Results: The relationship between critical care nurses and patients was revealed to be intense and it affected nurses' personalities and meanings in multiple ways. The core theme "syncytium" employs an analogy of the relevant term in physiology, which describes neighbouring cells that react and function in unison. This theme illustrated the constant simultaneous and reciprocal interaction between nurse and patient. A progressive course of suffering, development of understanding, acquisition of wisdom and personal advancement was conceptualized as another prevalent theme. This composite core theme was labeled "pain-acceptance-growth", and individual participants were found to experience different stages of this course. Moreover, spirituality issues were very prevalent in the narratives. Other themes, with several sub-themes each included: 1) empathy, 2) perception of role, 3) perceptions of patients. Conclusion: The lived experience of caring for critically ill individuals appears to be composite with profound effects on the personality, values and perceptions in life of nurses. Nurses appear to take part in the lived world of their patients, to share experiences and to learn from them.
Keywords: Critical care; Hermeneutic investigation; Nurses perceptions; Caring